FOLLOWER CHARACTERISTICS AND MOTIVATIONS IN A LEADERSHIP PROCESS - Wai Bing, Khuan; Abdull Kareem, Omar; Marzuki, Shahril@Charil; Yin Yin, Khoo (Management Research Journal, 2014)
The importance of followership studies cannot be underestimated. Industrial practitioners and academics are beginning to realize that followership is a distinct area of competency. Good followers obtain greater satisfaction, remuneration, self-actualization and other work benefits than poor followers. Having good followers enhances a leadership process leading to organizational performance, effectiveness and adaptability in a knowledge and technological advancing workplace. Knowing what shapes the characteristics of followers can improve feedback to leaders and help leaders adjust their behavior towards their employees. The main purpose of this study was to gain a better understanding of the characteristics of followership and its motivations. This study reported the findings of a qualitative study. Participants were employees in various public and private organizations. Data used in this exploration was collected through semi-structured interviews. Participants were asked to describe follower characteristics that effectively support organizational leaders, influence of the leader, and other factors besides leadership that influence a follower’s decision to follow the leader. This study should benefit organizations that want to improve their leadership training programmes by including effective followership strategies. Specific recommendations for further research are also suggested.